Implementasi Aplikasi Absensi Online dalam Penentuan Besaran Tunjangan Kinerja Pegawai Sekretariat Daerah Kabupaten Lampung Selatan - Nurhayati; Suradi; Amir, Aprilianto (Prodi Administrasi Bisnis FISIP Universitas Tulang Bawang Lampung, 2025)
One of the applications of technology in improving the effectiveness of ASN performance and discipline in South Lampung Regency is to use an android-based online attendance system, and the recapitulation of absences is the basis for providing ASN performance allowances based on South Lampung Regent Regulation Number 10 of 2024. The purpose of this study is to analyze the implementation of the application of online attendance in determining the amount of performance allowance for employees of the Regional Secretariat of South Lampung Regency. The methode of this research is qualitative with data collection method using observation and interviews with informants. The results of the study were concluded based on the aspects of goals and objectives that most employees understand that policies to improve discipline and develop a fair and measurable benefit system. From the aspect of resources, the readiness in each work unit is still uneven. The attitude of the implementers towards this policy is generally positive. Many employees have accepted the online attendance system as an effort to improve discipline and as part of a more transparent assessment system. The effectiveness of information delivery is still uneven. Some employees feel that the information is clear enough, but others feel that the explanations received are still limited, especially related to technical aspects. The suggestion for this study is that it is necessary to add indicators other than attendance, such as work quality, productivity, individual performance achievements, and team contribution. Improving facilities and infrastructure so that technical obstacles can be overcome immediately and provide technical guidance in the form of videos/tutorials, digital questions and answers, and practical pocket books, which are easy to understand by all levels of Civil Servants. Keywords: implementation, online attendance, performance allowance